(3TQM CdajI GHf eGdcs - (3CHhYHO Gddg HOQGdOjf eMeO Hf eMeO Hf YHO Gddg Hf eGdc GdWGFjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eMeO Hf CHj HcQ Hf GdTQa NGdO Hf YHOGdQMef Hf CMeO Hf QHjYI GdHYdHcj GdMfHdj GdCfUGQj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg SMHGfI HeG dg ef GdeMGeO Ydi eG CSHY ef fYeg GdHhGOj hGdYhGFO s
(3BNQgG (B:s
(3aGYde HCfg bO GfJgi YQVg ef gPG GdfXe, aEfg bO GTJed Ydi CYXe GdegeGJ ef Yde GdYQHjI Je GdcdGe HMeO Gddg s
(3CdajI GHf eGdc JSei CjVkG GdNdGUIs
(3GdeDda GHf fGXe GdCdajIs
(3GdfSNI ebGHdIs
(3aj GdeYgO fSNI CNQi GfXQ GdLRA GdChd (B61 (3fMh s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
Keywords: (3GdfMhs